1965
DOI: 10.1007/bf00186851
|View full text |Cite
|
Sign up to set email alerts
|

Brittle fracture propagation in rock under compression

Abstract: The results of studies of the initiation and propagation of fracture from a single Griffith crack in a biaxial compressive stress field are repe~ted, It is concluded that Griffith's theory of brittle fracture offers a reliable prediction of the fracture initiation stress but that the resulting fracture propagation from a single crack cannor account for the macroscopic fracture of a specimen. Some preliminary results of studies on crack arrays and on the effects of crack closure ha compression are presented. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 631 publications
(134 citation statements)
references
References 4 publications
6
125
0
3
Order By: Relevance
“…The mechanical properties evaluated during the tests are: Young's modulus _=_4GPa; uniaxial compressive strength _=_ 140MPa; fracture toughness _=_0.6MPa-m 1/2. Two methods of modelling the internal initial disk-like cracks were adopted: (1) embedding a thin disk-like inclusion into the resin block during casting. The inclusion consisted of two aluminium foil disks greased and put together and held within the sample by two cotton threads; (2) cutting two semi-circular slots of 0.3 mm thickness in two halves of the sample and then gluing the halves together (this method was used in [4]). In order to ensure the contact between the opposite faces of the crack, teflon or greased foil disks were inserted into the slots (According to the 2-D analysis [9], the initial cracks, i.e.…”
Section: Sample Preparation and Experimental Technique In The Experimentioning
confidence: 99%
“…The mechanical properties evaluated during the tests are: Young's modulus _=_4GPa; uniaxial compressive strength _=_ 140MPa; fracture toughness _=_0.6MPa-m 1/2. Two methods of modelling the internal initial disk-like cracks were adopted: (1) embedding a thin disk-like inclusion into the resin block during casting. The inclusion consisted of two aluminium foil disks greased and put together and held within the sample by two cotton threads; (2) cutting two semi-circular slots of 0.3 mm thickness in two halves of the sample and then gluing the halves together (this method was used in [4]). In order to ensure the contact between the opposite faces of the crack, teflon or greased foil disks were inserted into the slots (According to the 2-D analysis [9], the initial cracks, i.e.…”
Section: Sample Preparation and Experimental Technique In The Experimentioning
confidence: 99%
“…These cracks are oriented along the compression direction. This kind of fracture was addressed both in some theoretical models (Martin [37], Sammis and Ashby [38], Nikitin and Odintsev [39], Dyskin et al [40]) and experimentally (Martin [37], Sammis and Ashby [38], Hoek and Bieniawski [41], Gol'dshtein et al [42]). Let us consider the problem that serves as basis for some models of fracture in a porous material under biaxial loading ( [38], [42] and [43]).…”
Section: Biaxial Compression-extension Of a Perforated And Cracked Mamentioning
confidence: 99%
“…4. This follows from the fact that in a homogeneous material an inclined crack grows stably under compression, being oriented along the compression axis (Hock and Bieniawski [41], Horii and Nemat-Nasser [46], Brace and Bombolakis [56]) and unstably under tension oriented perpendicular to the tension axis (Erdogan and Sih [57]). Consequently, in this case we have a fold-type catastrophe.…”
Section: Strength Criteria and The Convexity Postulatementioning
confidence: 99%
“…Criteria that account for sliding friction between opposite faces of a closed crack have been proposed [McClintock (1963);Swedlow (1976A)], but have not been firmly established [Hoek (1965)]. Comparison and discussion of various criteria when applied to biaxial stress states have been presented by Shetty and coworkers (1981Shetty and coworkers ( , 1983.…”
Section: Such a Crack Would Remain In Its Own Plane As It Propagated mentioning
confidence: 99%
“…Hoek (1965) studied crack arrays and coalescence in compression because coalescence precedes failure in compression. Cooke (1982) found that microcracking precedes fracture under other conditions, as well.…”
Section: Microcracking: Initiation and Coalescencementioning
confidence: 99%